2021
DOI: 10.1186/s13287-020-02109-4
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming bioprocess bottlenecks in the large-scale expansion of high-quality hiPSC aggregates in vertical-wheel stirred suspension bioreactors

Abstract: Background Human induced pluripotent stem cells (hiPSCs) hold enormous promise in accelerating breakthroughs in understanding human development, drug screening, disease modeling, and cell and gene therapies. Their potential, however, has been bottlenecked in a mostly laboratory setting due to bioprocess challenges in the scale-up of large quantities of high-quality cells for clinical and manufacturing purposes. While several studies have investigated the production of hiPSCs in bioreactors, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 69 publications
3
74
1
Order By: Relevance
“…It was already reported that shear stress is an important regulator of germinal specification (Kumar et al, 2017;Wolfe et al, 2012). Although we expected lower and more homogeneous shear stress distribution using VWBRs when compared with other bioreactors (Borys et al, 2021;Croughan et al, 2016), we cannot exclude its impact on cell differentiation. Besides that, the VWBR has a unique mixing ability that allows a more efficient diffusion of the morphogens that might have an impact on cell specification (Croughan et al, 2016).…”
Section: Faster and Efficient Cerebellar Differentiation Is Promoted By Dynamic Culturecontrasting
confidence: 53%
“…It was already reported that shear stress is an important regulator of germinal specification (Kumar et al, 2017;Wolfe et al, 2012). Although we expected lower and more homogeneous shear stress distribution using VWBRs when compared with other bioreactors (Borys et al, 2021;Croughan et al, 2016), we cannot exclude its impact on cell differentiation. Besides that, the VWBR has a unique mixing ability that allows a more efficient diffusion of the morphogens that might have an impact on cell specification (Croughan et al, 2016).…”
Section: Faster and Efficient Cerebellar Differentiation Is Promoted By Dynamic Culturecontrasting
confidence: 53%
“…All cultures were maintained at 37°C in a humidified atmosphere with 5% CO 2 . The static expansion of these cells prior to bioreactor culture was performed according to methods previously described by Borys et al [ 17,18 ] In brief, hiPSCs were grown in Matrigel‐coated (Corning, 354 277) T‐flasks (Thermo Scientific, 156 599) in mTeSR1 medium supplemented with 10 μM Y‐27632. Media exchanges were performed daily with Y‐27632‐absent medium, and cells were passaged 3 days post‐inoculation (at approximately 80% confluency).…”
Section: Methodsmentioning
confidence: 99%
“…This geometry produces more uniform energy dissipation distributions and lower shear stress environments. [ 17,18 ] To expand upon our previous work, we modelled additional scales of the VW bioreactor including 0.5, 3, and 15 L at various agitations as shown in Figure 1. Scale‐up equations were developed from the models and used to determine a suitable operating range to culture human iPSCs (hiPSCs) where the VA EDR was maintained.…”
Section: Introductionmentioning
confidence: 99%
“…An impressive new study by Pandey and colleagues used a single-use 3 L BioBlu vessel to expand hiPSCs in 10 serial passages, culminating in a 93-fold overall expansion while maintaining pluripotency markers [ 175 ]. Despite these successes, studies are ongoing to determine the optimal conditions for hiPSC cultivation using novel reactor configurations (such as the innovative vertical-wheel bioreactor), optimal stirring speeds, inoculation and harvesting strategies [ 176 , 177 ].…”
Section: Generating Clinically Suitable Ipsc-rbcs For Transfusionmentioning
confidence: 99%